35‐2: 40x Current Variation Reduction Enabled by an External VT‐Compensation Scheme for AMOLED Displays using a 3T2C‐Pixel Circuit with Dual‐Gate TFTs. Issue 1 (30th May 2018) - Verschueren, Lynn; Ameys, Marc; De Roose, Florian; Steudel, Soeren; van der Steen, Jan-Laurens; Gelinck, Gerwin; Kronemeijer, Auke Jisk; Huang, Chin-Hai; Tsai, Chi-Chung; Huang, Yen-Yu; Yeh, Ming-Hua; Heremans, Paul; et al.
Abstract : A novel external VT compensation method, using a simple driving scheme, is presented, enabling high resolution, yet uniform displays, regardless of the size. The uniformity can be maintained for initial VT nonuniformities as well as VT shifts occurring during operation, like bias stress. The characterized display area shows a significant reduction in current variation, transforming 23% variation without compensation into 0.56% variation after calibration.